Acute effects of two different warm-up protocols on flexibility and lower limb explosive performance in male and female high level athletes - Tsolakis, C.; Bogdanis, G. C. (Journal of Sports Science & Medicine, 2012)
This study examined the effects of two different warm-up protocols on lower limb power and flexibility in high level athletes. Twenty international level fencers (10 males and 10 females) performed two warm-up protocols that included 5-min light jogging and either short (15s) or long (45s) static stretching exercises for each of the main leg muscle groups (quadriceps, hamstrings and triceps surae), followed by either 3 sets of 3 (short stretching treatment), or 3 sets of 5 tuck jumps (long stretching treatment), in a randomized crossover design with one week between treatments. Hip joint flexion was measured with a Lafayette goniometer before and after the 5-min warm-up, after stretching and 8 min after the tuck jumps, while counter movement jump (CMJ) performance was evaluated by an Ergojump contact platform, before and after the stretching treatment, as well as immediately after and 8 minutes after the tuck jumps. Three way ANOVA (condition, time, gender) revealed significant time (p < 0.001) and gender (p < 0.001) main effects for hip joint flexion, with no interaction between factors. Flexibility increased by 6. 8 ± 1.1% (p < 0.01) after warm-up and by another 5.8 ± 1.6% (p < 0.01) after stretching, while it remained increased 8 min after the tuck jumps. Women had greater ROM compared with men at all time points (125 ± 8° vs. 94 ± 4° p<0.01 at baseline), but the pattern of change in hip flexibility was not different between genders. CMJ performance was greater in men compared with women at all time points (38.2 ± 1.9 cm vs. 29.8 ± 1.2 cm p < 0.01 at baseline), but the percentage of change CMJ performance was not different between genders. CMJ performance remained unchanged throughout the short stretching protocol, while it decreased by 5.5 ± 0.9% (p < 0.01) after stretching in the long stretching protocol However, 8 min after the tuck jumps, CMJ performance was not different from the baseline value (p = 0.075). In conclusion, lower limb power may be decreased after long periods of stretching, but performance of explosive exercises may reverse this phenomenon.